2023
DOI: 10.56557/upjoz/2023/v44i103509
|View full text |Cite
|
Sign up to set email alerts
|

Study of Physico-chemical Parameters on a Fresh Water Pond of Orai, U.P., India

Abstract: Water plays a crucial role in sustaining human life but the ramifications of urbanization and industrialization result in the contamination of water sources, rendering them unsuitable for drinking and agricultural purpose. Ponds are classified as lentic water bodies, which get adversely affected by anthropogenic activities. The current investigation endeavours to assess the physico-chemical properties of the water of Mahil pond, a freshwater pond situated in the middle of the city (Orai). The present work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…During the South West Monsoon (SWM) season, Phosphate levels ranged from 1.0 to 1.1 mg/lit at both Loc. 1…”
Section: Phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the South West Monsoon (SWM) season, Phosphate levels ranged from 1.0 to 1.1 mg/lit at both Loc. 1…”
Section: Phosphatesmentioning
confidence: 99%
“…Physico-chemical parameters of freshwater reservoirs in India have been studied by several researchers in several parts of India. [1] conducted a study on Mahil pond in Orai and found that the water quality was unsuitable for drinking and sustaining resident organisms due to contamination from anthropogenic activities. Another study by [2] focused on Dandiganahalli dam and concluded that the water quality was moderate, with suitable conditions for agriculture, fisheries, and domestic use.…”
Section: Introductionmentioning
confidence: 99%